Wetland Weeds Causes, Cures and Compromises. - Romanowski, Nick. (Melbourne : CSIRO Pub., 2011)
A comprehensive guide to wetland weeds covering both native and introduced species.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wetland ecology -- New Zealand -- Handbooks, manuals, etc; Wetland restoration -- New Zealand -- Handbooks, manuals, etc; Environmental Studies; Science; Natural history; Aquatic weeds; Invasive plants; BUSINESS & ECONOMICS / Real Estate / General; Electronic books